Improving Developmental Screening, Discussion, and Referral in Pediatric Practice. (August 2019) - Bright, Melissa A.; Zubler, Jennifer; Boothby, Christina; Whitaker, Toni M.
Objective. Although pediatricians' use of standardized screening tools for identifying developmental delays has increased, only 63% of pediatricians report performing standardized screening as recommended. The purpose of the current quality improvement project was to improve developmental monitoring, screening, and referral for developmental concerns by pediatricians. Method. Twenty-eight pediatricians completed an in-person meeting, monthly webinars, and individualized feedback from an Expert Work Group on progress across a 3-month action period. Results. Statistically significant increases were observed in rates of autism screening, discussions of screening results with families, and referral following abnormal results. There was no statistically significant change in rates of general developmental screening. Comparing self-report with record review, pediatricians overestimated the extent to which they conducted discussion and referral. Conclusions. Universal screening for all children has yet to be achieved. The current project supports that practice-based improvements can be made and delineates some of the routes to success.